2016
DOI: 10.1108/ijlm-10-2013-0121
|View full text |Cite
|
Sign up to set email alerts
|

The use of an optimisation model to design a green supply chain

Abstract: Purpose – The purpose of this paper is to take the first step in solving environmental supply chain management issues. It proposes a green supply chain management (GSCM) model which would provide environmental benefits to the Thai rubber industry. To this end, a GSCM optimisation model was formulated, whereby the manufacturing processes of rubber products, along with their distribution and transportation, could be improved. The expected result is that total greenhouse gas emissions would be min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This study builds on the work of Chanchaichujit et al (2016) in which the authors developed a singleobjective optimization model for minimizing costs and GHG emissions for the Thai rubber supply chain. The multi-objective optimization model developed in this study includes objective function 1 for cost minimization, objective function 2 for GHG emission minimization and constraints 3-16 for the model constraints (See Tables A1 and B1 in the appendix).…”
Section: Research Methodology and Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…This study builds on the work of Chanchaichujit et al (2016) in which the authors developed a singleobjective optimization model for minimizing costs and GHG emissions for the Thai rubber supply chain. The multi-objective optimization model developed in this study includes objective function 1 for cost minimization, objective function 2 for GHG emission minimization and constraints 3-16 for the model constraints (See Tables A1 and B1 in the appendix).…”
Section: Research Methodology and Mathematical Formulationmentioning
confidence: 99%
“…Single objective linear programming models have one objective function requiring optimization. For example, Chanchaichujit et al (2016) used the single objective linear programming model to find the association between the quantity of rubber product flow between supply chain entities and the transportation mode and route, to minimize total GHG emissions. The authors considered GHG emissions and costs as two single objective functions and found the relationship between GHG emissions and costs to be in conflict with each other.…”
Section: Mathematical Modelling Based Approaches In Gscmmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar practices were carried out in Shim and Kumar (2010) and Islam (2018). Additionally, in accordance with Chanchaichujit et al (2016)'s suggestion that model validity and reliability may be conducted by a group of industry experts, the baseline model's simulated results were evaluated by related port operators. It can be concluded that the simulated results are certainly capable of providing realistic results.…”
Section: Model Validationmentioning
confidence: 99%
“…In this sense, several initiatives aimed at reducing the impact of logistics activities such as switching to use more environmentally friendly transport modes, consolidation of goods, and running an eco-efficient fleet can be implemented (Tacken et al , 2014). Thus, the fundamental shift is to properly integrate the environmental issues in planning the business strategies (Chanchaichujit et al , 2016). For example, the UK policy is aimed at stimulating the diffusion of low-impact vehicles based on fiscal incentives for hybrid and electric tractions (Brand et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%